Photodissociation dynamics of H2O and D2O via the D̃(1A1) electronic state. Issue 8 (6th January 2020) - Chang, Yao; Zhou, Jiami; Luo, Zijie; Chen, Zhichao; He, Zhigang; Yu, Shengrui; Che, Li; Wu, Guorong; Wang, Xingan; Yuan, Kaijun; Yang, Xueming
Abstract : We report the state-to-state dynamical features of photolysis of H2 O at 122.12 nm and that of D2 O at 121.95 nm, which are excited to the electronically excited D̃ state. Abstract : Photodissociation dynamics of H2 O and D2 O via the D̃ state by one-photon excitation have been investigated using the H/D atom Rydberg tagging time-of-flight technique. The TOF spectra of the H/D-atom product in both parallel and perpendicular polarizations have been measured. Product translational energy distributions and angular distributions have been derived from TOF spectra. By simulating these distributions, quantum state distributions of the OH/OD product as well as the state-resolved angular anisotropy parameters were determined. The most important pathway of H2 O/D2 O dissociation via the D̃ state leads to highly rotationally excited OH/OD(X, v = 0) products, while vibrationally excited OH/OD products with v ≥ 1 comprise only one third of the total OH/OD(X) population. The branching ratios of OH(A)/OH(X) and OD(A)/OD(X) have also been determined, 1.0/3.0 for H2 O at 122.12 nm and 1.0/2.2 for D2 O at 121.95 nm, which are reasonably consistent with the values predicted by the previous theory.